Pengaruh Komisaris Independen, Komite Audit Dan Kepemilikan Institusional Terhadap Opini Audit Asumsi Going Concern - Ravyanda, Mohammad Gusti; Wahyuni, Endang Dwi; Zubaidah, Siti (Universitas Muhammadiyah Malang)
This research aims to test and give empirical proofs of the influence of the existence of independentcommissioner, audit committee, and institutional ownership towards audit opinion. This researchused logistic regression analysis. The result of this research shows that independent commissioner, audit committee, and the composition of institutional ownership did not give influences toaudit opinion.Ke ywords: independent commissioner, audit committee, institutional ownership, audit goingconcern.